2017
DOI: 10.1002/ceas.12070
|View full text |Cite
|
Sign up to set email alerts
|

Advocating for Educational Standards in Counselor Licensure Laws

Abstract: As the counseling profession evolves, educational standards for counselor licensure must be standardized from state to state. In this article, the authors discuss historical and current influences and present an advocacy model that has been used to standardize educational requirements in state counselor licensure laws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A 2015 study found that fewer than half of undergraduate social work programs have coursework on substance use disorders [ 30 ]. Training and supervision post-graduation is needed, with clear regulatory recommendations for recertification and scope of practice [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 study found that fewer than half of undergraduate social work programs have coursework on substance use disorders [ 30 ]. Training and supervision post-graduation is needed, with clear regulatory recommendations for recertification and scope of practice [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Educational standards dialogue focused on strategies for advocating for educational standards in licensure laws (Lawson, Trepal, Lee, & Kress, 2017), an argument and pilot data in support of 60‐credit‐hour school counseling programs (Merlin & Brendel, 2017), and a proposal of spirituality as a ninth core curricular area (Bohecker, Schellenberg, & Silvey, 2017). Teixeira (2017) presented data suggesting that gatekeeping practices of counselor educators do not vary by the Council for Accreditation of Counseling and Related Educational Programs (CACREP) accreditation status.…”
Section: Professional Issuesmentioning
confidence: 99%
“…Nationwide licensure has helped the profession advance in many ways, but the lack of standardization in licensure requirements continues to be a barrier to those in the field. Social work and psychology have both endorsed national standards that specify educational expectations and that detail the scope of practice for their license holders that are consistent across the country (Lawson, Trepal, Lee, & Kress, 2017). Counseling has adopted no such set of standards, which places limits upon counselors in transferring licensure from one state to another.…”
Section: Licensure Portabilitymentioning
confidence: 99%
“…The NBCC, the American Mental Health Counselors Association (AMHCA), and the ACA all have concentrated advocacy efforts designed to advance this cause. Currently, these entities are focusing on the CACREP accreditation process as a mechanism to ensure the standardization of educational preparation of counselors and to create uniformity in state requirements (Lawson et al, 2017). In the past decade, Ohio, Kentucky, and North Carolina have changed their laws to require that independent practitioners must be graduates of a CACREP accredited program in order to obtain licensure.…”
Section: Licensure Portabilitymentioning
confidence: 99%